A Folk Theorem for Asynchronously Repeated Games - Yoon, Kiho (Econometrica, 2001)
We prove a Folk Theorem for asynchronously repeated games in which the set of players who may not be able to change their actions simultaneously. We impose a condition, the finite periods of inaction (FPI) condition, which requires that the number of periods in which every player has at least one opportunity to move is bounded. Given the FPI condition together with the standard nonequivalent utilities (NEU) condition, we show that every feasible and strictly individually rational payoff vector can be supported as a subgame perfect equilibrium outcome of an asynchronously repeated game.